Increased ISGylation in Cases of TBI-Exposed ALS Veterans. Issue 3 (28th December 2018) - Schwartzenburg, Joshua; Juncker, Meredith; Reed, Ryan; Desai, Shyamal
Abstract: Veterans who have served in the military are at a nearly 60% greater risk of being diagnosed with amyotrophic lateral sclerosis (ALS). Literature reports suggest that a history of traumatic brain injury (TBI) may be a risk factor for ALS in veterans. However, no diagnostic biomarkers are available for identifying ALS risk/development in TBI-exposed veterans. Here, using a Wes assay, we show that ISGylation, a conjugated form of interferon-stimulated gene 15 protein, is significantly elevated in the lumbar spinal cords (SC-Ls) of TBI-ALS compared with ALS veterans without a previous history of TBI (nonTBI-ALS). Although not as striking as in TBI-ALS veterans, ISGylation is also increased in nonTBI-ALS compared with normal veterans. Notably, no changes in ISGylation were seen in occipital lobe samples obtained from the same patients, suggesting that elevated ISGylation is distinct to ALS disease-specific SC-Ls. Moreover, we detected increased ISGylation in cerebral spinal fluid samples of TBI-ALS veterans. Other results using cultured lymphocyte cell lines show a similar trend of increased ISGylation in ALS patients from the general population. Together, these data suggest that ISGylation could serve as a diagnostic biomarker for TBI-ALS veterans, nonTBI-ALS veterans, and nonveterans affected by ALS.